Physicochemical Characteristics of Aerosol Particles Generated During the Milling of Beryllium Silicate Ores: Implications for Risk Assessment - Stefaniak, Aleksandr B.; Chipera, Steve J.; Day, Gregory A.; Sabey, Phil; Dickerson, Robert M.; Sbarra, Deborah C.; Duling, Mathew G.; Lawrence, Robert B.; Stanton, Marcia L.; Scripsick, Ronald C. (Journal of Toxicology and Environmental Health, Part A, 2008)
Inhalation of beryllium dusts generated during milling of ores and cutting of beryl-containing gemstones is associated with development of beryllium sensitization and low prevalence of chronic beryllium disease (CBD). Inhalation of beryllium aerosols generated during primary beryllium production and machining of the metal, alloys, and ceramics are associated with sensitization and high rates of CBD, despite similar airborne beryllium mass concentrations among these industries. Understanding the physicochemical properties of exposure aerosols may help to understand the differential immunopathologic mechanisms of sensitization and CBD and lead to more biologically relevant exposure standards. Properties of aerosols generated during the industrial milling of bertrandite and beryl ores were evaluated. Airborne beryllium mass concentrations among work areas ranged from 0.001 μg/m 3 (beryl ore grinding) to 2.1 μg/m 3 (beryl ore crushing). Respirable mass fractions of airborne beryllium-containing particles were < 20% in low-energy input operation areas (ore crushing, hydroxide product drumming) and > 80% in high-energy input areas (beryl melting, beryl grinding). Particle specific surface area decreased with processing from feedstock ores to drumming final product beryllium hydroxide. Among work areas, beryllium was identified in three crystalline forms: beryl, poorly crystalline beryllium oxide, and beryllium hydroxide. In comparison to aerosols generated by high-CBD risk primary production processes, aerosol particles encountered during milling had similar mass concentrations, generally lower number concentrations and surface area, and contained no identifiable highly crystalline beryllium oxide. One possible explanation for the apparent low prevalence of CBD among workers exposed to beryllium mineral dusts may be that characteristics of the exposure material do not contribute to the development of lung burdens sufficient for progression from sensitization to CBD. In comparison to high-CBD risk exposures where the chemical nature of aerosol particles may confer higher bioavailability, respirable ore dusts likely confer considerably less. While finished product beryllium hydroxide particles may confer bioavailability similar to that of high-CBD risk aerosols, physical exposure factors (i.e., large particle sizes) may limit development of alveolar lung burdens.